Children's Health in London and Luton (CHILL) cohort: a 12-month natural experimental study of the effects of the Ultra Low Emission Zone on children's travel to school - Christina Xiao; James Scales; Jasmine Chavda; Rosamund E. Dove; Ivelina Tsocheva; Helen E. Wood; Harpal Kalsi; Luke Sartori; Grainne Colligan; Jessica Moon; Esther Lie; Kristian Petrovic; et al. (BMC, 2024)
Abstract Background The Ultra-Low Emission Zone (ULEZ), introduced in Central London in April 2019, aims to enhance air quality and improve public health. The Children's Health in London and Luton (CHILL) study evaluates the impact of the ULEZ on children's health. This analysis focuses on the one-year impacts on the shift towards active travel to school. Methods CHILL is a prospective parallel cohort study of ethnically diverse children, aged 6-9 years attending 84 primary schools within or with catchment areas encompassing London's ULEZ (intervention) and Luton (non-intervention area). Baseline (2018/19) and one-year follow-up (2019/20) data were collected at school visits from 1992 (58%) children who reported their mode of travel to school 'today' (day of assessment). Multilevel logistic regressions were performed to analyse associations between the introduction of the ULEZ and the likelihood of switching from inactive to active travel modes, and vice-versa. Interactions between intervention group status and pre-specified effect modifiers were also explored. Results Among children who took inactive modes at baseline, 42% of children in London and 20% of children in Luton switched to active modes. For children taking active modes at baseline, 5% of children in London and 21% of children in Luton switched to inactive modes. Relative to the children in Luton, children in London were more likely to have switched from inactive to active modes (OR 3.64, 95% CI 1.21-10.92). Children in the intervention group were also less likely to switch from active to inactive modes (OR 0.11, 0.05-0.24). Moderator analyses showed that children living further from school were more likely to switch from inactive to active modes (OR 6.06,1.87-19.68) compared to those living closer (OR 1.43, 0.27-7.54). Conclusions Implementation of clean air zones can increase uptake of active travel to school and was particularly associated with more sustainable and active travel in children living further from school.